2018
DOI: 10.1111/1468-4446.12504
|View full text |Cite
|
Sign up to set email alerts
|

Strategic ignorance and global governance: an ecumenical approach to epistemologies of global power

Abstract: How can we account for the role of ignorance and knowledge in global governance? It is a contention of earlier scholarship in international relations and political sociology that knowledge production is tightly coupled with rational action – regardless of whether knowledge widely influences different stakeholders or not. This scholarship equally tends to assume an ignorance‐knowledge binary relationship that associates ignorance with powerlessness and knowledge with power. This is a view we dispute. Calling fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…It has been suggested that the vexed debate over climate change and decarbonization has been worsened by a political era of “alternative truths” and “fake news” (Innes, 2020; Mallard & McGoey, 2018). This debate can be understood through the “knowledge‐ignorance paradox,” in which “the exponential growth in the volume and complexity of information” has, somewhat ironically, produced ignorance (Ungar, 2000, p. 298).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the vexed debate over climate change and decarbonization has been worsened by a political era of “alternative truths” and “fake news” (Innes, 2020; Mallard & McGoey, 2018). This debate can be understood through the “knowledge‐ignorance paradox,” in which “the exponential growth in the volume and complexity of information” has, somewhat ironically, produced ignorance (Ungar, 2000, p. 298).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that strategic ignorance can be purposive—that is, keeping certain aspects of knowledge away from particular actors can result in a positive outcome. Thus, rather than assuming that ignorance consists simply of a lack of knowledge, it is more useful to explore how ignorance is produced, and to what ends (Mallard & McGoey, 2018). While McGoey’s (2012a, 2012b) concept of strategic ignorance can certainly be assigned to some of the disruptions to action on climate change, we suggest that this can also be seen as a reflexive movement.…”
Section: Introductionmentioning
confidence: 99%
“…Although this point is rarely developed explicitly, such artful cultivation of ignorance is arguably woven intricately through apparatuses of anticipatory government (Mallard & McGoey, 2018). The anticipation of retrospection introduced earlier in this paper (Caduff, 2014;Hinchliffe et al, 2017) clearly forms an important component of the 'temptations' towards strategic ignorance which Adrian describes, and similar anxieties about future accountability for present day decisions feature prominently in existing accounts of the mobilization of ignorance in response to regulatory scrutiny (for instance Heimer, 2012;McGoey, 2007;Pénet, 2018).…”
Section: Safer Not To Know?mentioning
confidence: 81%
“…Scholars "build" both categorizations and ignorance 41 that interact with other forms of knowledge in a highly unpredictable and unexpected manner. Their endeavors result in revealing some truths about the studied phenomena and simultaneously offering misinterpretations thereof, 42 thus opening up venues for new research. Reflexivity and the ability to critically address the earlier categorizations is scholars' professional and moral 43 responsibility.…”
Section: Categorizationsmentioning
confidence: 99%